Titanium mesh bone grafting combined with pedicle screw internal fixation for treatment of Ku[Combining Diaeresis]mmell disease with cord compression: A case report and literature review. Issue 36 (September 2018) - Mei, Liangwei; Sang, Wenhua; Chen, Zhenzhong; Lou, Chao; Zheng, Lin; Jin, Kangtao; Huang, Wenjun; He, Dengwei
Abstract: Rationale: In 1891, Dr. Hermann Kümmell, a German surgeon, described a clinical entity characterized by the development of progressive painful kyphosis following an asymptomatic period of months or years after a minor spinal trauma, leading to a gradual collapse of the vertebra and dynamic instability, ultimately progressing to kyphosis with prolonged back pain and/or paraparesis. To date, the main pathologic eliciting event remains unclear, and no standard treatment or single effective treatment are available for Kümmell disease. Patient concerns: A 74-year-old woman presented with severe back pain and numbness of both legs for approximately 2 months. Diagnoses: According to the clinical symptoms and imaging examinations, the patient was diagnosed with stage III Kümmell disease. Interventions: The patient underwent titanium mesh bone grafting combined with pedicle screw internal fixation. Outcomes: Postoperative kyphosis was corrected, and the vertebra was reconstructed. Lessons: Kümmell disease is not a rare complication of osteoporotic vertebral compression fractures, and treatment of each patient must be individualized. The application of titanium mesh bone grafting combined with pedicle screw internal fixation is an effective treatment option for stage III Kümmell disease.